Metastable underwater superhydrophobicity - Poetes, Rosa; Holtzmann, Kathrin; Franze, Kristian; Steiner, Ullrich (Physical Review Letters, 2010)
Superhydrophobicity is generally considered to be a thermodynamically stable wetting state. The stability of the plastron (the thin air film separating the substrate from the water in the superhydrophobic state) was studied in underwater experiments. The plastron exhibited a rapid decay after a well defined onset time, which was found to be dependent on the immersion depth. The plastron decay is explained in terms of a model, which is based on confocal microscopy measurements. The limited underwater plastron stability explains the rarity of permanently submerged superhydrophobic surfaces in nature and limits their scope for commercial applications. © 2010 The American Physical Society.
CRIS-Team Scopus Importer:2020-08-12